Shade and cooling effect of colonnade in low-rise street canyon in tropical climate - Lam, Jiih Kui (2012)
The shophouse buildings in Malaysia, which flank commercial streets, are of low-rise planning. The building height is controlled according to council’s plot ratio, but is always built on the development needs. Colonnade has been a part of the shophouse design regulations to provide overhead rain shelter and for sun shading. Provision of 7.5 feet (2.25 m) is the minimum depth. The main aim of this study is to investigate the potential of colonnade depth to lower the overall air temperature in the urban street microclimate. At the same time, fundamental climatic criteria of overhead shading elements and provision of enough space as a pedestrian thoroughfare in the urban must be fulfilled. Ecotect is used to run the shading analysis. Envelope Ratio and CTTC model are used for air temperature reduction simulations. In a H/W 0.25 street, adequate overhead shading from 1100 to 1600 can only be achieved with Dc/Hc 1.5 and above. This translates to 6 meters of colonnade depth. Colonnade in H/W 2 street with Dc/Hc 1 and above provides comfortable shades throughout the day. To lower the air temperature, the optimum colonnade depth to street width ratio is C/W 0.6. Deeper colonnade will give no significant microclimate improvement. It is found that the ideal colonnade ratio is C/W 0.2 to 0.6. Existing urban code requires Dc/Hc 0.75. In a north-south street, it is only able to offer adequate shade of 2 meter from 1230 to 1400. In a east-west street, it is only able to give 1 to 1.5 meter of shade, during the extreme case of summer and winter solstice. Existing colonnade depth of 2.25 meter and street width of 15 meter will give C/W 0.15. In both shallow and deep canyons, the effect in reducing the air temperature is limited.